Self-reported symptoms and exercise-induced asthma in the elite athlete - Rundell, K. W.; Im, J.; Mayers, L. B.; Wilber, R. L.; Szmedra, L.; Schmitz, H. R. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purpose of this study was to compare self-reported symptoms for exercise-induced asthma (EIA) to postexercise challenge pulmonary function test results in elite athletes. Methods: Elite athletes (N = 158; 83 men and 75 women; age: 22 +/- 4.4 yr) performed pre- and post-exercise spirometry and were grouped according to postexercise pulmonary function decrements (PFT-positive, PFT-borderline, and PFT-normal for EIA). Before the sport/environment specific exercise challenge, subjects completed an EIA symptoms-specific questionnaire. Results: Resting FEV1 values were above predicted values (114-121%) and not different between groups. Twenty-six percent of the study population demonstrated >10% postexercise drop in FEV1 and 29% reported two or more symptoms. However, the proportion of PFT-positive and PFT-normal athletes reporting two or more symptoms was not different (39% vs. 41%). Postrace cough was the most reported symptom, reported significantly more frequently for PFT-positive athletes (P < 0.05). Sensitivity/specificity analysis demonstrated a lack of effectiveness of self-reported symptoms to identify PFT-positive or exclude PFT-normal athletes. Postexercise lower limit reference ranges (MN-2SDs) were determined from normal athletes for FEV1, FEF25-75% and PEF to be -7%, -12.5%, and -18%, respectively. Conclusion: Although questionnaires provide reasonable estimates of EIA prevalence among elite cold-weather athletes, the use of self-reported symptoms for EIA diagnosis in this population will likely yield high frequencies of both false positive and false negative results. Diagnosis should include spirometry using an exercise/environment specific challenge in combination with the athlete's history of asthma symptoms.